Kreativitas Guru PAI dalam Meningkatkan Kemampuan Membaca Al-Qur’an Siswa di SMP IT Ar Roja Kisaran - Rizki Amaliyah Putri; Dedi Masri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to describe the creativity of Islamic Religious Education (PAI) teachers in improving students' Quran reading skills at SMP IT Ar Roja Kisaran. This study used a qualitative approach with a phenomenological type, with data collection techniques through observation, interviews, and documentation, and analyzed using the Miles and Huberman model. The results showed that most students were able to read the Quran fluently. Only a few students lagged behind their peers, namely those who still did not understand the correct tajwid and still stuttered in reading the Quran, namely in grade VII. The creativity of Islamic Religious Education (PAI) teachers was manifested through the use of hijaiyah flash cards, the use of smart TV as interactive learning media, and the involvement of peers in the learning process. In addition, the tahsin and tahfiz programs implemented routinely every morning can strengthen the habit of reading the Quran correctly through the talaqqi method and memorization repetition. These consistent and gradual efforts showed an increase in students' Quran reading skills, both in terms of fluency and accuracy of tajwid.